Procedural Extensions of SQL: Understanding their usage in the wild - Gupta, Surabhi; Ramachandra, Karthik (PVLDB, 2021)
Procedural extensions of SQL have been in existence for many decades now. However, little is known about their magnitude of usage and their complexity in real-world workloads. Procedural code executing in a RDBMS is known to have inefficiencies and limitations; as a result there have been several efforts to address this problem. However, the lack of understanding of their use in real workloads makes it challenging to (a) motivate new work in this area, (b) identify research challenges and opportunities, and (c) demonstrate impact of novel work. We aim to address these challenges with our work. In this paper, we present the results of our in-depth analysis of thousands of stored procedures, user-defined functions and triggers taken from several real workloads. We introduce SQL-ProcBench, a benchmark for procedural workloads in RDBMSs. SQL-ProcBench has been created using the insights derived from our analysis, and thus represents real workloads. Using SQL-ProcBench, we present an experimental evaluation on several database engines to understand and identify research challenges and opportunities. We emphasize the need to work on these interesting and relevant problems, and encourage researchers to contribute to this area.